CHARACTERISTIC PROPERTIES OF PROTEIN PEROXIDATION AND ENZYME ACTIVITY OF GLUTATHIONE SYSTEM IN NEWBORNS FROM DIFFERENT ECOLOGICAL ZONES IN IVANO-FRANKIVSK REGION - Кочерга, З.Р.; Швець, Л.С.; Косило, Н.В. (World of Medicine and Biology, 2017)
The purpose of our research was to study protein peroxidation and enzyme activity of glutathione system in newborns under the influence of ecotoxicants. Primarily, by means of comprehensive assessment of anthropogenic pollution the following four districts of Ivano-Frankivsk region were chosen: Kosiv district (relatively ecologically clean), chemically contaminated Kalush and Burshtyn, and Sniatyn district (the area of intensive radiological control); the increased levels of xenobiotics were found in water, soil and air. We have carried out the investigation of protein peroxidation and enzyme activity of glutathione system in 108 newborns from the above mentioned residence areas. Neutral aldehyde- and ketone-derivatives prevailed in neonates from Burshtyn. Basic aldehyde- and ketone-derivatives with maximum absorption at a wavelength of 530 nm prevailed in newborns from Kosiv district. Study of glutathione system enzymes showed decreasing activity of glutathione peroxidase, glutathione reductase and glutathione-S-transferase in neonates from Burshtyn and Kalush that proves the exhaustion of adaptation mechanisms in terms of a long-term impact of xenobiotics on the fetus’ organism. The obtained results may indicate better functioning of protective anti-radical systems in babies from ecologically friendly zones of Kosiv district.